A STUDY OF THE PROCESS OF IMPLEMENTING THE SELECTIVE SEPARATION OF WASTE IN A DRINK DISTRIBUTOR - Rodrigues, Diego; Terazzi, Luis Fernando (Revista Interface Tecnológica, 2020)
The objective of this research is to conduct a study, identifying the processes, benefits and difficulties for implementing a selective selection of residues in a beverage distributor. In order to achieve this purpose, the qualitative approach is adopted, operationalized by a case study. To carry out the data collection, semi-structured interviews were carried out with four employees, it is worth mentioning that the interviewees are involved with the researched subject. After conducting the analysis of the interviews, it was identified that the company suffered from the accumulation of garbage, polluted environment, loss of time and lack of organization, where through these factors the professionals decided to implement the selective separation. As main results, it can be seen that with the implementation of selective separation the company obtained a more organized environment, leaving the space accessible, passable, avoiding possible accidents.